2016
DOI: 10.1016/j.diabres.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Overweight adolescents with type 2 diabetes have significantly higher lipoprotein abnormalities than those with type 1 diabetes

Abstract: Aim Diabetes-associated glucoregulatory derangements may precipitate atherogenesis in childhood and CVD risk, particularly with obesity. We aimed to delineate lipoprotein profile differences between children with type 1 and 2 diabetes who are overweight/obese. Methods Data were obtained from electronic medical records of patients ≥85th BMI percentile with type 1 (n=159) and type 2 (n=77) diabetes, ages 12–19y. Group differences were evaluated by correlations and general linear modeling analysis, adjusting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
5
12
0
Order By: Relevance
“…In this study, HDL was increased in the more acute STZ model of diabetes (Table ) but reduced in the more chronic LCR obesity model (Table ). This is similar to humans, where HDL levels are relatively preserved in young T1DM and reduced in chronic T2DM . PGC‐1 α is increased by treatment with LY379269 (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, HDL was increased in the more acute STZ model of diabetes (Table ) but reduced in the more chronic LCR obesity model (Table ). This is similar to humans, where HDL levels are relatively preserved in young T1DM and reduced in chronic T2DM . PGC‐1 α is increased by treatment with LY379269 (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Our group has previously demonstrated that overweight and obese children with T2DM have significantly more atherogenic lipoprotein profiles even when compared to overweight and obese children with T1DM [7] , suggesting an inherently increased risk for atherogenicity in children with T2DM. This has been also supported by a larger multi-center trial [12] .…”
Section: Discussionmentioning
confidence: 86%
“…The clustering of risk factors such as insulin resistance, increased body mass index (BMI), and physical inactivity are more prevalent in children with T2DM than in those with T1DM [5] , [6] and has generated significant information on the pathophysiologic link between T2D and CVD. Moreover, overweight/obese children with T2DM have a higher risk of adverse lipoprotein profiles compared to overweight/obese T1DM children [7] .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…With aggravating insulin resistance, the concentration and mean size of VLDL-P increase, whereas LDL and HDL particle sizes decrease [ 23 ]. Abnormal lipoprotein profiles, including higher small dense LDL and lower large buoyant HDL fractions, indicate poor glycemic control in overweight adolescents with type 2 diabetes [ 24 ]. A recent article by Mackey et al [ 25 ] described the association between lipoprotein particles and the incidence of type 2 diabetes in a multicenter prospective cohort study, indicating that the number and size of VLDL-P were significantly associated with the incidence of type 2 diabetes in patients with atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%